Analysis of economic and social development in Barbados : a model for small island developing states (ECLAC [Port of Spain]TT, 2001)
Reviews the significant economic and social development over the past four decades. Draws particular attention to achievements in the diversification of the country's productive apparatus and the transformation of its historically monocultural profile based on sugarcane to one of a modern, competitive, service-oriented economy. Notes that tourism and financial services are major components of the economy, and as well as this, there is also a modest manufacturing sector.
Keywords: ECONOMIC AND SOCIAL DEVELOPMENT